Warm Teachers Make Enthusiastic Students: How Teachers Build Positive Relationships With Students - Rosyidah, Fairuz Syifa; Rifameutia, Tjut; Djoumoi, Ahmed (Universitas Negeri Malang, 2024)
In addition to their teaching responsibilities, teachers must possess social competence, particularly in interacting effectively with their students. Previous research highlights a significant correlation between the quality of teacher-student relationships and the level of conflict within the classroom. Therefore, teacher competence in fostering positive relationships with students is essential for creating an environment of positive discipline. This research aims to enhance teachers' understanding of the fundamental principles of positive relationships through a training program titled